An Autopsy Based Correlation Study about Determination of Sex from the Combined Length of Sternum (Manubrium + Body) in the Central India Indore Region (M.P.) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Accurate determination of Sex from skeleton has been a critical issue in medico legal cases and the accuracy depends on the type of material available and methods applied. Bony remains and decomposed bodies are very important in forensic investigation. Sternum bone is very important bone for age and sex determination in the advance stage of decomposition and from mutilated, fragmented bodies Sternum is a bone which is easily retrievable even from the advance decomposed body and also from the bundle of bone. In our study Total 632 subject for sex having 350 male and 282 female of age >25 years was taken data analysis was done by using SPSS software and relevant statistical test was applied. In our study bisexual variation in relation to length of manubrium was found conclusive.
Keywords: Anthropometry; Bisexual variation; Sex determination; Combined length (M+B) length